The Influence of Product Quality and Brand Image on Customer Loyalty through Customer Satisfaction on Preloved Products - Marsudi Marsudi; Fika Fitriasari; Nuryanti Nuryanti (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to determine partially or simultaneously the effect of product quality and brand image on customer loyalty with customer satisfaction as an intervening variable on preloved bag products at the online store Fafacordelia store. The population in this study were all customers of the online shop Fafacordelia store with a sample of 100 respondents. The sampling technique is through a sampling technique with the criteria of customers who have purchased the product more than 2 times by distributing questionnaires through the google form. The results of this study indicate that product quality and brand image have a positive effect on customer loyalty, as well as customer satisfaction as an intervening variable on customer loyalty of preloved bags at Fafacordelia store partially or simultaneously. Based on this research, it can be concluded that product quality and brand image have a positive and significant effect on customer loyalty of preloved bags with customer satisfaction as the intervening variable.